The Perceptions of Cancer Patients Regarding the Causes and Preventability of Unplanned Hospital Admissions. (October 2020) - Meisenberg, Barry R.; Karpman, Mitchell; Tan, Jessica; Parlacoski, Stephanie; Rhule, Jane; Moxley, John
Abstract : Objective: The objective of this study was to determine the attitudes of oncology patients regarding the causes and preventability of unplanned hospitalizations. Methods: Convenience sample using a 36-question survey instrument adapted from prior studies of hospital readmissions. Results: A total of 95 evaluable patients answered >75% of survey items. Majorities (64%) agreed that they desired to avoid the admission, but disagreed (79%) that their own admission was preventable. Patients did not generally express lack confidence in their overall self-management abilities (only 36% agreed) or dissatisfaction with the level of home support, emotional or equipment (only 11% to 26% agreed). Patients did not complain of an inability to access their oncology care team (only 14% agreed), yet a strong majority (79%) endorsed the idea that emergency department visits represent the "quickest and easiest way to get needed care" and that the "hospital is the best place for me when I am sick" (60%). Overall, 79% indicated that their oncology care team directed them to visit the emergency department for evaluation. Most results did not differ by demographic factors. Conclusions: These results differ from previous results that use methods other than a direct patient survey to determine the preventability or root causes of unplanned hospital admissions/ or readmissions. Accordingly, patient support programs may not address the root causes of unplanned admissions. The use of the emergency department for unplanned care may represent local culture and institutions planning reduction efforts should include patent perceptions to plan a holistic solution. Abstract : Supplemental Digital Content is available in the text.